2006
DOI: 10.1007/s11104-005-2950-8
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Nitrogen Placement and Tillage on NO, N2O, CH4 and CO2 Fluxes from a Clay Loam Soil

Abstract: To evaluate the impact of N placement depth and no-till (NT) practice on the emissions of NO, N 2 O, CH 4 and CO 2 from soils, we conducted two N placement experiments in a long-term tillage experiment site in northeastern Colorado in 2004. Trace gas flux measurements were made 2-3 times per week, in zero-N fertilizer plots that were cropped continuously to corn (Zea mays L.) under conventional-till (CT) and NT. Three N placement depths, replicated four times (5, 10 and 15 cm in Exp. 1 and 0, 5 and 10 cm in Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
86
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(101 citation statements)
references
References 27 publications
15
86
0
Order By: Relevance
“…Other studies, in agreement with the present findings, also showed higher soil N 2 O emission from NT than from CT soils (Rice & Smith, 1982;Smith et al, 2001;Yamulki & Jarvis, 2002;Liu et al, 2006;Liu et al, 2007;Rochette et al, 2008;Gomes et al, 2009). The main reasons, according to those authors, is related to soil compaction and higher WFPS, resulting from the higher soil moisture, and in some cases, lower soil porosity in NT.…”
Section: Soil N 2 O Emissionsupporting
confidence: 92%
See 1 more Smart Citation
“…Other studies, in agreement with the present findings, also showed higher soil N 2 O emission from NT than from CT soils (Rice & Smith, 1982;Smith et al, 2001;Yamulki & Jarvis, 2002;Liu et al, 2006;Liu et al, 2007;Rochette et al, 2008;Gomes et al, 2009). The main reasons, according to those authors, is related to soil compaction and higher WFPS, resulting from the higher soil moisture, and in some cases, lower soil porosity in NT.…”
Section: Soil N 2 O Emissionsupporting
confidence: 92%
“…In turn, soil tillage affects the majority of the N 2 Oemission-controlling soil variables and higher emissions of this GHG have usually been reported in soils under NT than under CT (Rice & Smith, 1982;Liu et al, 2007). This finding has been attributed to a lower O 2 diffusion due to soil compaction (Vinten et al, 2002;Baggs et al, 2003;Liu et al, 2006), mainly in periods of frequent and intense rainfall (Jantalia et al, 2006), and to a higher microbial biomass activity, consuming O 2 and forming anaerobic microsites (Baggs et al, 2006). However, most results regarding N 2 O emission were obtained in temperate soils, and limited information is available for tropical and subtropical Oxisols, where favorable soil physical properties of soil structure and aeration as well as rapid water-infiltration may restrict N 2 O production and emission by denitrification (Jantalia et al, 2006;Metay et al, 2007;Jantalia et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This result is probably related to several aspects: the presence of easily decomposable soybean residues on the soil surface, higher WFPS values (Figure 1a), higher stocks of labile soil organic carbon (Campos, 2006) and higher microbial biomass in NT compared to CT, as reported previously at the same experimental site (Fabrizzi et al, 2008). The higher soil CO 2 -C flux under NT compared to CT, especially at sites under longstanding no-tillage systems, have been reported elsewhere (Yamulki & Jarvis, 2002;Campos, 2006;Liu et al, 2006;Oorts et al, 2007). This could be related to an improvement in soil quality and biomass input potential in the conservation system, compared to conventional systems (Amado et al, 2007).…”
Section: Soil Co 2 -C Fluxsupporting
confidence: 84%
“…Usually, short-term CO 2 -C flux after tillage is higher in the CT plots (Reicosky & Lindstrom, 1993;La Scala et al, 2006) or in some cases similar (Sanhueza et al, 1994;Fortin et al, 1996;Campos, 2006;Costa et al, 2008) to the ones registered in the NT plots. On the other hand, some researchers found higher emissions in NT than in CT systems (Hendrix et al, 1998;Ball et al, 1999), which indicates that the effect of soil tillage on soil CO 2 -C flux could be related to: duration, season, soil moisture and temperature, soil type, the mechanism of soil C stabilization and C stock (Liu et al, 2006). This study aimed to investigate the effect of tillage systems on soil CO 2 -C flux in the fall season, determined by static and dynamic chambers, in a Rhodic Hapludox in Cruz Alta, Rio Grande do Sul State, Southern Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Implementation of no-tillage can increase soil CO 2 emissions due to the higher water content maintenance in the soil surface layer which results in greater soil biological activity. Other authors have also determined higher CO 2 emissions at no-tillage compared to conventional tillage [25,41]. In 2013, during the winter wheat growing season, soil C-CO 2 emissions did not differ significantly between different tillage treatments with crops.…”
Section: Discussionmentioning
confidence: 88%